Biosynthesis and genetic engineering of phenazine-1-carboxylic acid in Pseudomonas chlororaphis Lzh-T5 - Liu, Kaiquan; Li, Zhenghua; Liang, Xiaoli; Xu, Yanpeng; Cao, Yufei; Wang, Ruiming; Li, Piwu; Li, Ling (Frontiers in Microbiology, 2023)
Phenazine-1-carboxylic acid (PCA) is a biologically active substance with the ability to prevent and control crop diseases. It was certified as a pesticide by the Ministry of Agriculture of China in 2011 and was named “Shenzimycin.” Lzh-T5 is a Pseudomonas chlororaphis strain found in the rhizosphere of tomatoes. This strain can produce only 230 mg/L of PCA. We used LDA-4, which produces the phenazine synthetic intermediate trans-2,3-dihydro-3-hydroxyanthranilic acid in high amounts, as the starting strain. By restoring phzF and knocking out phzO, we achieved PCA accumulation. Moreover, PCA production was enhanced after knocking out negative regulators, enhancing the shikimate pathway, and performing fed-batch fermentation, thus resulting in the production of 10,653 mg/L of PCA. It suggested that P. chlororaphis Lzh-T5 has the potential to become an efficiency cell factory of biologically active substances.